RISK ASSESSMENT FOR HEALTH OF THE POPULATION FROM AIR POLLUTION BY EMISSIONS OF NOVOKUZNETSK PILOT-PRODUCTION PLANT OF TECHNOLOGICAL EQUIPMENT - Дмитрий Вячеславович Суржиков; Вера Викторовна Кислицына; Роман Анатольевич Голиков; Раушания Нафиловна Суржикова (Медицина в Кузбассе, 2019)
Subject. The subject of the study is the atmospheric emissions of Novokuznetsk pilot-production plant of technological equipment.